Absence of causative genetic association between Helicobacter pylori infection and glaucoma: a bidirectional two-sample mendelian randomization study - Zhang, Yan; Huang, Yihong; Wu, Yuyu; Zhang, Jinying; Chen, Wanzhu; Xu, Danfeng; Guo, Maosheng (Frontiers in Genetics, 2024)
Helicobacter pylori infection and the onset of glaucoma, the causality of this association remains uncertain due to the susceptibility of observational studies to confounding factors and reverse causation.analysis was conducted to assess the causal connection between H. pylori infection and glaucoma. Glaucoma was categorized into primary open-angle glaucoma (POAG), normal tension glaucoma (NTG), and pseudo-exfoliation glaucoma (PEG). Various methods, including inverse variance weighted, MR-Egger regression, weighted median, and mode-based estimator, were employed for effect estimation and pleiotropy testing. To enhance result robustness, a sensitivity analysis was performed by excluding proxy single nucleotide polymorphisms.Results: Genetic predisposition for H. pylori infection has no causal effect on glaucoma: (OR 1.00; 95% CI 0.95-1.06, p = 0.980), (OR 0.97; 95% CI 0.86-1.09, p = 0.550), and (OR 0.99; 95% CI 0.90-1.08, p = 0.766) with POAG, NTG, and PEG, respectively. An inverse MR showed no causal effect of POAG, NTG, and PEG on H. pylori infection (OR 1.01; 95% CI 0.97-1.05, p = 0.693), (OR 1.00; 95% CI 0.98-1.03, p = 0.804), and (OR 0.99; 95% CI 0.96-1.01, p = 0.363), respectively. Heterogeneity (P > 0.05) and pleiotropy (P > 0.05) analysis confirmed the robustness of MR results.These results indicated that there was no genetic evidence for a causal link between H. pylori and glaucoma, suggesting that the eradication or prevention of H. pylori infection might not benefit glaucoma and vice versa.